Can I touch your hair? : poems of race, mistakes, and friendship - Latham, Irene; Waters, Charles, 1973- (Carolrhoda Books, 2018)
Shares a collection of poetry for children highlighting racial diversity and friendship. Told from the perspectives of a young white girl and a young African American boy.